American Muslim Women, Religious Authority, and Activism - Krista Riley (American Journal of Islam and Society, 2014)
In American Muslim Women, Religious Authority, and Activism: More Than a Prayer, Juliane Hammer traces recent conversations around gender and religion within American Muslim communities. Taking as a starting point the mixedgender Friday prayer led by Amina Wadud in 2005, the author examines how questions of gendered religious authority have been negotiated through interpretations of scripture and religious laws, challenges to constructions of tradition and community, contestations surrounding prayer spaces, and representations of Muslim women in the media and autobiographical narratives. 100 The American Journal of Islamic Social Sciences 31:1 The result is a valuable and insightful mapping of some of the major scholars, activists, and public figures engaged in work related to women, gender, and Islam in North America. Based on an analysis of texts produced by female American Muslim scholars and writers since the 1980s and especially within the past decade, the book highlights women’s contributions to debates around women-led prayer, Qur’anic interpretations, women’s spaces in mosques, and women’s leadership within Muslim communities, among other issues. Hammer acknowledges that of many of the texts she studies have a “progressive” leaning, but frames this as itself a research finding that reflects the perspectives and voices most likely to be published or otherwise highlighted within an American context ...